Upaya Pengelolaan dan Pengembangan Objek Wisata Pantai Batu Gajah Kabupaten Tapanuli Tengah - Heru Aldi Hendrawan Barutu; Rusmauli Simbolon; Ade Putera Arif Panjaitan; Bambang T.J Hutagalung; Tio R J Nadeak (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze efforts to manage and develop the Batu Gajah Beach tourist attraction and to identify the challenges faced in managing and developing the Batu Gajah Beach tourist attraction. This research uses a qualitative research method with a descriptive approach and data collection techniques through observations, interviews and documentation of several informants, namely managers, the community and tourists. Researchers describe that the Batu Gajah Beach tourist attraction has attractive tourism potential with its natural scenery, as well as management efforts in managing and developing the Batu Gajah Beach tourist attraction such as facilities and infrastructure, maintenance and conservation, security and safety, promotion and marketing, and financial management.